Aproveitamento do glicerol residuário da produção de biodiesel em fermentações destinadas a produção de goma xantana e biossurfactantes - Pinheiro, Taís Magalhães Abrantes (2013)
The present work used glycerol as a carbon source to obtain bio-based product from fermentation with microorganisms. It was used seven different microorganisms in order to convert glycerol into biopolymers. The microorganisms tested were Lactobacillus casei shirota, Klebisiella sp., Xanthomonas campestris, and four yeasts from the Antarctic continent whose codes are L26, L32, L33, L35. For each microorganism exploratory tests were held in order to select strains capable of converting glycerol in bio-based product of interest. Each test was carried out according to the needs of microorganisms. The maximum production of xanthan was 1.1 g /L. The evaluation of the molar mass of the gum was satisfactory and spectrometry in the infrared region revealed similarities between the gum produced and the commercial ones.